Factor analysis in education research - Kožemiakina, Veronika; Sičiūnienė, Viktorija (Lietuvos matematikos rinkinys, 2021)
Using factor analysis was studied the variables structure of the 2005 national student’s achievements research questionnaire and reduced quantity of primal variables in questionnaire. Statistical analysis was done using SPSS 13.0. During research there were extracted 4 indicators: class and school environment, social and economical situation, student attitude towards mathematic and his achievement in mathematic and mathematics teacher work style. Base oneself on factors obtained from indicator is presented recommendations.